A Multimodality Analysis - Annisa Ayu Elfhariyanti; Lisetyo Ariyanti; Laily Maulida Septiana Harti (Pioneer: Journal of Language and Literature, 2021)
Advertisement is a public media to promote a product or a service. Shampoo advertisements, especially the ones made for women, always show the advantages that the product gives to the customers. This study construed beauty standard in shampoo advertisements through the visual and linguistic elements, and found the differences in how they construe the beauty standard. This study used four different brands taken from Cosmopolitan magazine from 2016 to 2018. The brands are Love, Beauty and Planet, Loreal Extraordinary Oil, Treseme and Garnier Fructis. This study used the Multimodality approach using two modes, visual and linguistic elements. This study used Generic Structure Potential by Cheong (2004) to divide the linguistic and visual elements, then used Kress and Leeuwen's visual grammar to analyze the visual element (2006) and used Halliday's metafunction to analyze the linguistic elements (1978). Then this study analyzed the interplay of the visual and linguistic elements to construe beauty standards in society using O'Halloran SF-MDA (2008). The study shows that all of the shampoo advertisements have different ways to construe beauty standard in society through the visual and linguistic elements.